Needle-based ultrasonic diagnostic tool - Soorani, Mitra (2018)
Designing extremely small sized photoacoustic transducers can be very important in medical applications to perform in vivo imaging or to measure elastic properties of tissue that is hard to access externally, for example deep-seated tissue or tissue that is in very small and narrow cavities. The medical applications range from in vivo biopsy, in order to prevent of unnecessary biopsies, to the monitoring of cancer therapy, to investigation of the progression of disease in vivo as well as microsurgical guidance. Recently, a three-layered thin-film Fabry-Perot Interferometer (FPI) based structure has been used as a transducer to generate acoustic waves and launch them into cells under study. Brillouin oscillations in the cells were measured in the gigahertz (GHz) range which allowed high resolution imaging of living cells. The approach used in this study demonstrated the potential of providing the new insights in cell biology and it offers advantages over other mechanical imaging techniques in terms of speed, signal amplitude, and resolution. In this thesis, a method for extending this technique is described, where small FPI transducer (sub-mm) is fabricated on the tip of a single mode fibre to produce a wide range of mechanical frequencies with the focus on biomedical applications. The FPI comprises of an optical cavity or spacer sandwiched between two parallel partially reflecting mirrors. In the current study, a novel pump-probe technique is used for the generation and detection of acoustic waves via the same transducer, while two separate transducers are currently used in other studies; one for generation and one for detection of acoustic waves.